USE SUNFLOWER OIL PRODUCED BY JSC «SHYMKENTMAY» AT THE DEVELOPMENT OF TECHNOLOGY OF EMULSION PRODUCT - M.K. Kassymova,; Z.I. Kobzhasarova,; G.E. Orymbetova,; G. Nurynbetova,; Anita Blija, (Academic Scientific Journal of Chemistry, 2020)
On the basis of the conducted researches on factors of formation of consumer properties of emulsion products, recipes and technology of low-calorie emulsion sauces have been developed. On the basis carried out of the studies the factors of the formation of consumer properties of emulsion products of special purpose, recipes and technology for obtaining low-calorie emulsion sauces were developed. The expediency and effectiveness of the use of deodorized refined vegetable oils of JSC "Shymkentmai" were substantiated. An organoleptic evaluation of the experimental emulsion products were carried out in comparison with the traditional ones, which were evaluated according to the following parameters: appearance, consistency, odor and taste. It has been established that a of fat content 35% emulsion product on the basis of sunflower oil produced by JSC «Shymkentmai» with a plant additive were characterized by a higher value of the total quality index due to the delicate taste and absence of foreign flavors. It is revealed that the calorie content of the new emulsion product is significantly reduced by reducing the prescription amount of vegetable oil, while maintaining high organoleptic parameters. Low amounts of protein in the formulations of the new emulsion product should be considered as a positive moment, as emulsion product is a sauce that is served to the main dish, including meat, fish and poultry